2017
DOI: 10.1007/s11629-016-4230-x
|View full text |Cite|
|
Sign up to set email alerts
|

Decadal glacial lake changes in the Koshi basin, central Himalaya, from 1977 to 2010, derived from Landsat satellite images

Abstract: Changes in glacial lakes and the consequences of these changes, particularly on the development of water resources and management of glacial lake outburst flood (GLOF) risk, has become one of the challenges in the sustainable development of high mountain areas in the context of global warming. This paper presents the findings of a study on the distribution of, and area changes in, glacial lakes in the Koshi basin in the central Himalayas. Data on the number of glacial lakes and their area was generated for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Lake changes in Ladakh show a heterogeneous pattern varying from increasing to decreasing lake sizes and recurrent fluctuations. This is similar to observations made by Ashraf et al (2017) for the adjacent Karakoram, by Shrestha et al (2017) for the Koshi basin and by Nie et al (2018) along the Himalayan arc.…”
Section: Discussionsupporting
confidence: 90%
“…Lake changes in Ladakh show a heterogeneous pattern varying from increasing to decreasing lake sizes and recurrent fluctuations. This is similar to observations made by Ashraf et al (2017) for the adjacent Karakoram, by Shrestha et al (2017) for the Koshi basin and by Nie et al (2018) along the Himalayan arc.…”
Section: Discussionsupporting
confidence: 90%
“…The shadow and cloudiness in the high mountain areas with a monsoon climate complicated the selection of cloud and shadow free satellite data. The Landsat scenes acquired were from the post-monsoon season because the sizes of glacial lakes are stationary and changes are minor just after monsoon season; further, this season has less cloud cover and perennial snow coverage [9,36,48,49]. The acquired Landsat scenes of the study area had low cloud coverage (less than 10%) or were cloud-free.…”
Section: Datamentioning
confidence: 99%
“…Compared with other regional studies [1,9], the glacial lakes in the Nepal Himalaya account for~27% and~15% of the total number and area of glacial lakes, respectively, in the third pole, and~31% and~18% of the total number and area of glacial lakes, respectively, in the entire Himalaya (Table 4). A recent study of glacial lakes in the Koshi river basin overestimated the total number and area of the lakes because it did not apply a threshold for the maximum glacier-lake distance to map glacial lakes, and also, the quality control and assurance procedures were not explained [48].…”
Section: Mapping and Comparison With The Previous Studiesmentioning
confidence: 99%
“…Several previous studies were conducted in the Nepal Himalaya, focusing on the development of such lakes (e.g., [31,[34][35][36]), hazard assessments (e.g., [13,30,34,37,38]), and community involvement in glacial lake research (e.g., [39,40]). Most of these studies demonstrated the development of glacial lakes usually on a decadal basis [8,41,42], and were regionally aggregated [11]. Furthermore, these studies were glacier or lake specific [13,24,43,44] or used one time satellite imagery [45].…”
Section: Introductionmentioning
confidence: 99%